Export-Led Growth in Malaysian Agriculture: A VAR Approach - Abdullah, Ahmad Zainuddin (Universiti Putra Malaysia Press, 1993)
This paper investigates the export-growth relationship for the Malaysian agricultural sector using a threevariable vector autoregressive (VAR) model. The model was subjected to three different causality tests procedure: Granger causality, Hsiao's technique and variance decomposition. The results indicate that growth of gross domestic product (GOP) causes exports in two of the three test procedures employed.